2011
DOI: 10.1007/s10661-011-1902-4
|View full text |Cite
|
Sign up to set email alerts
|

Beach geomorphic factors for the persistence of subsurface oil from the Exxon Valdez spill in Alaska

Abstract: Oil from the 1989 Exxon Valdez oil spill persists in some of the Prince William Sound (Alaska) beaches and continues to be a potential threat to the fauna. This paper reports a field investigation during the summer of 2008 of groundwater flow and solute transport in a tidal gravel beach in Smith Island, Prince William Sound. The beach contains oil on one side, the left side (facing landward). Field measurements of water table, salinity, and tracer (lithium) concentration were obtained for an approximate durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The nearly anoxic conditions in this low-permeability layer negatively affected the ability of microbes to degrade the oil. In another study, Xia and Boufadel (2011) identified beach slope as a geomorphic factor that influenced hydrologie flushing rates locally within a beach. It is particularly challenging to characterize subsurface hydrology in the extremely heterogeneous shoreline environments of PWS without subsurface investigation, and our results indicate almost no difference between the rates of occurrence of heavier subsurface oil at sites with and the rates at those without stream mouths or evidence of signiflcant groundwater flow.…”
Section: Factormentioning
confidence: 99%
See 1 more Smart Citation
“…The nearly anoxic conditions in this low-permeability layer negatively affected the ability of microbes to degrade the oil. In another study, Xia and Boufadel (2011) identified beach slope as a geomorphic factor that influenced hydrologie flushing rates locally within a beach. It is particularly challenging to characterize subsurface hydrology in the extremely heterogeneous shoreline environments of PWS without subsurface investigation, and our results indicate almost no difference between the rates of occurrence of heavier subsurface oil at sites with and the rates at those without stream mouths or evidence of signiflcant groundwater flow.…”
Section: Factormentioning
confidence: 99%
“…Lastly, hydrologie processes such as wave backwash, groundwater flow, and surface-water runoff are generally more energetic on a steeper intertidal slope. In studies of a highly exposed gravel beach with heavy remaining subsurface oil, the findings of Xia and Boufadel (2011) imply that hydrologie processes are more efflcient at oil flushing and nutrient replenishment on steep gravel beaches. A steep nearshore zone, with its accompanying deeper water, allows waves to break near the shore or on the intertidal zone.…”
Section: Introductionmentioning
confidence: 99%
“…Boufadel (2010, 2011) and reported that subsurface oil persisted in the beach with two hydraulically different layers and small fresh groundwater flow. Xia and Boufadel (2011) found that mild beach slop and armoring of beach surface were the major elements for oil persistence. Oil persistent in beaches are possibly re-dissolved or dispersed into the water column and may be potential threat to marine organisms (Michel et al, 2009;Peterson et al, 2003;Short et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To check for the possible limitation of interfacial area, the specific surface area per unit mass was evaluated for each of the islands by using the grain size distribution obtained from the literature. The average diameter of the sediment was 4.2 mm (Li and Boufadel, 2010), 7 mm (Xia et al, 2010), and 9.4 mm (Xia and Boufadel, 2011) for Eleanor Island (EL056C), Knight Island (KN114A), and Smith Island (SM006B), respectively. The grain size distribution of Eleanor Island presented in this study is not from a same beach as was used in the Venosa et al (2010) study.…”
Section: Resultsmentioning
confidence: 99%